Longitudinal Relations between Emotion Restraint Values, Life Stress, and Internalizing Symptoms Among Vietnamese American and European American Adolescents - Tsai, William (J Clin Child Adolesc Psychol, 2019)
OBJECTIVE: Recent research has documented cultural differences in the extent and manner in which various forms of emotion regulation are linked with psychological well-being. Most of these studies, however, have been cross-sectional, nor have they directly examined the values underlying the use of emotion regulation. The present study examined emotion restraint values and their interactions with life stress in predicting internalizing symptoms across time among Vietnamese American and European American adolescents. The study focused on adolescence as a critical developmental period during which life stress and internalizing symptoms increase significantly. METHOD: Vietnamese American (n = 372) and European American (n = 304) adolescents’ levels of emotion restraint values, internalizing symptoms, and stress were assessed at two timepoints six months apart. RESULTS: Results indicated differential associations between emotion restraint values, stress, and symptoms over time for the two groups. For Vietnamese American adolescents, emotion restraint values did not predict depressive, anxiety, or somatic symptoms. For European American adolescents, emotion restraint values predicted higher somatic symptoms but buffered against the effects of interpersonal stress on anxiety and depressive symptoms. CONCLUSIONS: These results provide increased understanding of the role of values related to emotion restraint in shaping adolescent internalizing symptoms and responses to stress across cultural groups. Implications of the findings for guiding intervention efforts are discussed.